Representation of Women in Academic Orthopaedic Leadership: Where Are We Now?. Issue 1 (16th January 2022) - Bi, Andrew S.; Fisher, Nina D.; Bletnitsky, Nikolas; Rao, Naina; Egol, Kenneth A.; Karamitopoulos, Mara
Abstract: Background: Women have long been underrepresented in orthopaedic surgery; however, there is a lack of quantitative data on the representation of women in orthopaedic academic program leadership. Questions/purposes: (1) What is the proportion of women in leadership roles in orthopaedic surgery departments and residency programs in the United States (specifically, chairs, vice chairs, program directors, assistant program directors, and subspecialty division chiefs)? (2) How do women and men leaders compare in terms of years in position in those roles, years in practice, academic rank, research productivity as represented by publications, and subspecialty breakdown? (3) Is there a difference between men and women in the chair or program director role in terms of whether they are working in that role at institutions where they attended medical school or completed their residency or fellowship? Methods: We identified 161 academic orthopaedic residency programs from the Accreditation Council for Graduate Medical Education (ACGME) website. Data (gender, length of time in position, length of time in practice, professorship appointment, research productivity as indirectly measured via PubMed publications, and subspecialty) were collected for chairs, vice chairs, program directors, assistant program directors, and subspecialty division chiefs in July 2020 to control for changes in leadership. Information not provided by the ACGME and PubMed was found using orthopaedic program websites and the specific leader's curriculum vitae. Complete data were obtained for chairs and program directors, but there were missing data points for vice chairs, assistant program directors, and division chiefs. All statistical analysis was performed using SPSS using independent t-tests for continuous variables and the Pearson chi-square test for categorical variables, with p < 0.05 considered significant. Results: Three percent (4 of 153) of chairs, 8% (5 of 61) of vice chairs, 11% (18 of 161) of program directors, 27% (20 of 75) of assistant program directors, and 9% (45 of 514) of division chiefs were women. There were varying degrees of missing data points for vice chairs, assistant program directors, and division chiefs as not all programs reported or have those positions. Women chairs had fewer years in their position than men (2 ± 1 versus 9 ± 7 [95% confidence interval -9.3 to -5.9]; p < 0.001). Women vice chairs more commonly specialized in hand or tumor compared with men (40% [2 of 5] and 40% [2 of 5] versus 11% [6 of 56] and 4% [2 of 56], respectively; X 2 (9) = 16; p = 0.04). Women program directors more commonly specialized in tumor or hand compared with men (33% [6 of 18] and 17% [3 of 18] versus 6% [9 of 143] and 11% [16 of 143], respectively; X 2 (9) = 20; p = 0.02). Women assistant program directors had fewer years in practice (9 ± 4 years versus 14 ± 11 years [95% CI -10.5 to 1.6]; p = 0.045) and fewer publications (11 ± 7 versus 30 ± 48 [95% CI -32.9 to -5.8]; p = 0.01) than men. Women division chiefs had fewer years in practice and publications than men and were most prevalent in tumor and pediatrics (21% [10 of 48] and 16% [9 of 55], respectively) and least prevalent in spine and adult reconstruction (2% [1 of 60] and 1% [1 of 70], respectively) (X 2 (9) = 26; p = 0.001). Women program directors were more likely than men to stay at the same institution they studied at for medical school (39% [7 of 18] versus 14% [20 of 143]; odds ratio 3.9 [95% CI 1.4 to 11.3]; p = 0.02) and trained at for residency (61% [11 of 18] versus 42% [60 of 143]; OR 2.2 [95% CI 0.8 to 5.9]; p = 0.01). Conclusion: The higher percentage of women in junior leadership positions in orthopaedic surgery, with the data available, is a promising finding. Hand, tumor, and pediatrics appear to be orthopaedic subspecialties with a higher percentage of women. However, more improvement is needed to achieve gender parity in orthopaedics overall, and more information is needed in terms of publicly available information on gender representation in orthopaedic leadership. Clinical Relevance: Proportional representation of women in orthopaedics is essential for quality musculoskeletal care, and proportional representation in leadership may help encourage women to apply to the specialty. Our findings suggest movement in an improving direction in this regard, though more progress is needed.